Roles of real-time three-dimensional transesophageal echocardiography in peri-operation of transcatheter left atrial appendage closure. Issue 4 (January 2017) - Zhou, Qing; Song, Hongning; Zhang, Lan; Deng, Qing; Chen, Jinling; Hu, Bo; Wang, Yijia; Guo, Ruiqiang
Abstract : Abstract: Left atrial appendage (LAA) closure is a new treatment option for the prevention of stroke in patients with nonvalvular atrial fibrillation (AF). Conventional 2-dimensional transesophageal echocardiography (2D TEE) has some limitations in the imaging assessment of LAA closure. Real-time 3-dimensional transesophageal echocardiography (RT-3D TEE) allows for detailed morphologic assessment of the LAA. In this study, we aim to determine the clinical values of RT-3D TEE in the periprocedure of LAA closure. Thirty-eight persistent or paroxysmal AF patients with indications for LAA closure were enrolled in this study. RT-3D TEE full volume data of the LAA were recorded before operation to evaluate the anatomic feature, the landing zone dimension, and the depth of the LAA. On this basis, selection of LAA closure device was carried out. During the procedure, RT-3D TEE was applied to guide the interatrial septal puncture, device operation, and evaluate the occlusion effects. The patients were follow-up 1 month and 3 months postclosure. Twenty-eight (73.7%) patients with AF received placement of LAA occlusion device under RT-3D TEE. Eleven cases with single-lobe LAAs were identified using RT-3D TEE, among which 4 showed limited depth. Seventeen cases showed bilobed or multilobed LAA. Seven cases received LAA closure using Lefort and 21 using LAmbre based on the 3D TEE and radiography. The landing zone dimension of the LAA measured by RT-3D TEE Flexi Slice mode was better correlated with the device size used for occlusion ( r = 0.90) than 2D TEE ( r = 0.88). The interatial septal puncture, the exchange of the sheath, as well as the release of the device were executed under the guidance of RT-3D TEE during the procedure. The average number of closure devices utilized for optimal plugging was (1.11 ± 0.31). There were no clinically unacceptable residual shunts, pericardial effusion, or tamponade right after occlusion. All the patients had the device well-seated and no evidence of closure related complications in the follow-up. Assessment of LAA morphology by RT-3D TEE contributes to the decision of device selection for the closure. 3D TEE is a reliable imaging modality to guide device operation and assess on-site closure.